Penggunaan Framework Codeigniter dalam Perancangan Sistem Laporan Maintenance Mesin di Bagian Joint Quality Analisis (JQA) PT Gajah Tunggal Tbk - Dyas Yudi Priyanggodo; Bambang Irawan; Rohmat Taufiq; Yani Sugiani (Jurnal SITECH : Sistem Informasi dan Teknologi, 2025)
The drug sales process still uses manual recording in managing stock and sales transactions, making it difficult for store owners to directly monitor drug availability and reduce errors in recording. This study aims to design a web-based drug inventory and sales information system at Ayu Drug Store to address the existing problems. Data collection methods used observation, interviews, and archiving, while system analysis used the PIECES method. The system was developed with a Prototype model using the Laravel 10 framework, PHP, and MySQL. The results of the study proved that this system successfully increased work efficiency, reduced recording errors, and accelerated transaction and reporting processes. This system also provides easy access to information for store owners and employees. Thus, the system developed is expected to significantly improve operational performance and service quality at Ayu Drug Store, while also serving as a foundation for further technological development in the future.